Analisis Manajemen Ketersediaan Suku Cadang Bengkel X di Kota Makassar - Muhammad Alfisar; Muhammad Farid; Saharuna Saharuna (Industrial Engineering Study Program, Pattimura University, 2024)
This research aims to find out: (1) What is the description of spare parts availability management, (2) What factors can influence spare parts availability. This research was carried out at one of the car repair shops in the city of Makassar, namely the Mahaputra Alauddin repair shop. This research uses qualitative research methods, with a case study approach. The data collection technique uses in-depth interviews with sources consisting of workshop heads, supervisors, staff, mechanics and consumers. The results of this research reveal 1) a picture of spare parts availability management, namely a) workshop spare parts supplies come from the Mahaputra Alauddin workshop warehouse, Mahaputra Bandang workshop, and the central warehouse on Jl. Ir. Sutami, b) ordering spare parts refers to data on the availability and release of spare parts on the current day, then ordering goods is immediately carried out, c) the application used to order spare parts is the Telegram application, d) if spare parts are needed and not available, then the staff the warehouse will coordinate spare parts orders to the Mahaputra Bandang Workshop; 2) Factors that influence the availability of spare parts include a) the unavailability of all types of spare parts for various vehicle brands, b) lack of staff accuracy in the ordering process.